Social skills group training in adolescents with disabilities: A systematic review. (June 2022) - Gilmore, Rose; Ziviani, Jenny; Chatfield, Mark D.; Goodman, Sarah; Sakzewski, Leanne
Abstract: Background: Group social skills interventions (GSSIs) are offered to youth with Autism Spectrum Disorder (ASD) to improve social functioning. This systematic review focused on the adolescent population, including a wider range of disabilities. Aims: To evaluate effectiveness of GSSIs at improving social functioning in adolescents with congenital, acquired or developmental disabilities. Methods and procedures: Databases, trial registries and dissertations were systematically searched and a meta-analysis of randomized controlled trials conducted. Study screening, risk-of-bias assessment and Grading of Recommendations Assessment, Development and Evaluation were completed. Outcomes and results: Sixteen studies (n = 1119), 15 with adolescents with ASD and one with brain tumor survivors, revealed GSSIs reduced social impairment on the Social Responsiveness Scale (mean difference (MD) 9.68, 95% CI 5.63–13.73; P < 0.001), increased social skills on the Social Skill Improvement System Rating Scales (SMD 0.38, 95% CI 0.10–0.65; P = 0.007), and improved adolescent social knowledge on the Test of Adolescent Social Skills (MD 7.43 points, 95% CI 5.36–9.50; P < 0.001). Conclusions and implications: There is moderate certainty evidence that GSSIs improve social responsiveness, social skills and knowledge, and low certainty of evidence to improve social participation for adolescents with ASD. High quality randomized studies are required to inform clinical practice with adolescents with other disabilities. What this paper adds: Current evidence for group social skills interventions (GSSIs) is for adolescents with autism (ASD). GSSIs likely improve social knowledge and reduce impairments in adolescents with ASD, however the effect of GSSIs on social participation is not well understood. Only one randomized trial investigated GSSIs in another population of adolescents, highlighting the need for more high-quality studies including adolescents with other disabilities. Highlights: Evidence for group social skills interventions (GSSIs) is for autism (ASD). GSSIs likely improve social knowledge in adolescents with ASD. GSSIs likely reduce impairments in adolescents with ASD. The effect of GSSIs on social participation is not well understood. More trials investigating GSSIs in populations other than ASD are required.